2020
DOI: 10.1101/2020.07.01.183020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

6-Thioguanine blocks SARS-CoV-2 replication by inhibition of PLpro protease activities

Abstract: AbstractA recently emerged betacoronavirus, SARS-CoV-2, has led to a global health crisis that calls for the identification of effective therapeutics for COVID-19 disease. Coronavirus papain-like protease (PLpro) is an attractive drug target as it is essential for viral polyprotein cleavage and for deconjugation of ISG15, an antiviral ubiquitin-like protein. We show here that 6-Thioguanine (6-TG) inhibits SARS-CoV-2 PLpro-catalyzed viral polyprotein cleavage and ISG15 deconjuga… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
1
24
2
Order By: Relevance
“…S4 ), but all other drugs were ineffective. These results contradict with several published studies which demonstrated that disulfiram 44 , 6-TG 45 , 46 and ebselen 43 inhibited the protease activity of MERS-CoV and SARS-CoV PLpro in vitro , and 6-TG inhibited SARS-CoV-2 replication at submicromolar levels 47 . The discrepancy may stem from different substrates used for assessing inhibitor efficacy.…”
Section: Resultscontrasting
confidence: 99%
“…S4 ), but all other drugs were ineffective. These results contradict with several published studies which demonstrated that disulfiram 44 , 6-TG 45 , 46 and ebselen 43 inhibited the protease activity of MERS-CoV and SARS-CoV PLpro in vitro , and 6-TG inhibited SARS-CoV-2 replication at submicromolar levels 47 . The discrepancy may stem from different substrates used for assessing inhibitor efficacy.…”
Section: Resultscontrasting
confidence: 99%
“… 17 19 Indeed, some recent studies have focused primarily on targeting this activity to modulate the immune evasion of SARS-CoV-2. 20 22 In addition, because PLpro resides in a multidomain, membrane-bound protein, it is possible that compounds that inhibit the soluble protease may not have as great of an effect on the full nsp3 protein and therefore on viral replication. 23 In the studies in Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Klemm et al showed that benzodioxolane analogs 3j , 3k , and 5c , which inhibit SARS-CoV PL pro in the sub-micromolar range ( Báez-Santos et al, 2014 ) displayed similar inhibitory activity against SARS-CoV-2 PL pro ( Klemm et al, 2020 ). Two other compounds have been shown to inhibit SARS-CoV-2 PL pro in vitro , inhibiting viral production in cell culture: the approved chemotherapy agent 6-Thioguanine ( Swaim et al, 2020 ), and the anti-dengue protease inhibitor mycophenolic acid ( Kato et al, 2020 ).…”
Section: Druggability Characterization Of Sars-cov-2 Proteinsmentioning
confidence: 99%